The Basic Principles of Studying Works of Church Music in the Classes of the Student Choral Group - Kyfenko, Anna; Sopova, Dana; Holian, Khristina (Educological discourse, 2024)
The article analyses the main principles of studying works of church music in the classes of the student choral group, namely: the principle of the dominant role of the word and the subordinate meaning of music in spiritual songs, which develops theological understanding of the Bible text meaning and its professional delivery to the listener; the principle of arrangement, ensemble coherence and emotional restraint in singing which is based on the purity of intonation, ensemble coherence of all elements of choral sonority, emotional statics of the content of church hymns; the principle of the unity of singing and spiritual and moral education and training consists in the formation of moral, religious, empathetic qualities of the individual through the singing of church works that bring inner peace, harmony, peace, which is confirmed by the holy fathers of the Church Basil the Great, John Chrysostom, Athanasius the Great, blessed Augustine; the charismatic principle is based on the concept of “charisma”, which means exceptional giftedness in a certain field, including musical, vocal and choral abilities, the best qualities of a leader-organizer, leader of a student choir. Empirical research data show that church choral music as a phenomenon of national culture is oriented towards absolutely spiritual values, appeals to the inner spiritual world of a person, comprehension of earthly existence, concentration on self-discipline, introspection of feelings and thoughts. It is emphasised that church choral music is a highly moral, didactic basis, the biblical plot of the text of choral works carries educational potential (ethos), a complex of spiritual and moral ideas. Church singing, unlike other forms of art, is a carrier of the highest spirituality and morality. Singing church works promotes the development of vocal and creative skills: musical and auditory activity, vocal hearing, sharpness of intonation, rhythm, diction, memory, sense of ensemble, etc.